Interfaces between linguistics, termilogy and documentation - Tálamo, Maria de Fátima Gonçalves Moreira; Lara, Marilda Lopes Ginez de (Faculdade de Filosofia e Ciências, 2010)
Presents reflections on the interface between Linguistics, Documentation and Terminology, highlighting the aspects that are related to the proposal of pedagogical procedures aimed at the education and training of the documentalist. The superiority of natural language is underscored as the original place of the signified to show its privileged role for accessing knowledge, to which teaching and learning methods should correspond, leading to an understanding of the place of specialist languages as well as those of documentalist activities. The proposal of Documentary Linguistics is discussed which, in dialogue with Terminology, seeks to highlight the functions of onomasiological paths – from emission to conceptualization (from the concept to the term) – alongside semasiological ones – from reception and interpretation (from the term to the concept), in the education and training of the documentalist. This is followed by a brief synthesis of a didactic-pedagogical experiment.